Partial Characterisation and Some Properties of a Thermophilic Bacterium Isolated from a Petroleum Reservoir in Sarawak, Malaysia - You, Li Ling (1999)
The hypertbermophilic bacteria (MRU5) was isolated from an oil-producing well in Sarawak. Malaysia. MRU5 is strictly anaerobic and was grown in enrichment media which were been degassed with CO2:N2 (80:20). By Gram and spore staining, MRU5 was found to be a gram negative, non-spore producing bacteria. Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) revealed the shape of the bacteria to be irregular and coccoid which occurs singly, in pairs or clumps. The bacteria measures 0.75µm in diameter and is surrounded by an outer sheath coating. MRU5 was found to grow best at pH 7 and 10% salinity with the optimal temperature range of between 90°C to 100°C. MRU5 was grown in xylose, glucose, fructose, arabinose, lactose, and sucrose. From the results obtained, xylose was the most efficiently utilised fermentable carbon source. Growth of the microorganism is supported by yeast extract. End products such as organic acids and H2S were produced by fermentation of carbon sources but none of the tested solvents were produced. This microorganism is able to reduce oil viscosity by producing organic acids. This means that MRU5 has the potential to be ecologically important for enhancing oil recovery. The modified Gompertz equation was found to be appropriate to model the growth of bacterium MRU5 at different medium compositions and culture conditions.